A Hybrid GA-PSO Approach Based on Similarity for Various Types of Economic Dispatch Problems - Guvenc, U.; Duman, S.; Saracoglu, B.; Ozturk, A. (Elektronika ir Elektrotechnika, 2011)
Economic dispatch problem is an optimization problem where objective function is highly nonlinear. In this paper, an efficient method based on hybrid genetic algorithm- particle swarm optimization (GA-PSO) for economic dispatch (ED) problem is proposed. In the proposed method, children created by using similarity measurement between mother and father chromosomes relationship. The feasibility of the proposed approach is demonstrated for solve various types of economic dispatch (ED) problems in power systems such as, economic dispatch with valve point (EDVP) effects, the ED of generators with prohibited operating zones and ED with only fuel options and it is compared in the recent literature. The study results show that the proposed approach is more efficient in finding higher quality solutions in various type ED problems. Ill. 3, bibl. 20, tabl. 10 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.108.2.155